Unternehmensfinanzierung in Holland - Cornelis F. Scheffer (Kredit und Kapital, 1970)
Financing Business in Holland The article deals first with the possibilities of "internal" financing from the cash-flow: residual depreciation allowances, rational use of working funds, self-financing. In the following remarks on external financing of firms by way of credit, etc., the institutional situation and organizational arrangements in the Netherlands are thoroughly ventilated. The main emphasis in this presentation is placed on direct credits and government aid for the financing of small and medium-sized firms. In connection with financing by equity capital, the activity cf investment and other finance companies is dealt with. Strong emphasis is placed on the assessment of the expected liquidity situation and future profit chances, which provide a good basis for examining the creditability of a firm.
Keywords: 330